Home » » Find the value of k if $$\frac{k}{\sqrt{3} + \sqrt{2}}$$ = k$$\sqrt{3 - 2}$$

# Find the value of k if $$\frac{k}{\sqrt{3} + \sqrt{2}}$$ = k$$\sqrt{3 - 2}$$

### Question

Find the value of k if $$\frac{k}{\sqrt{3} + \sqrt{2}}$$ = k$$\sqrt{3 - 2}$$

### Options

A) 3

B) 2

C) $$\sqrt{3}$$

D) $$\sqrt 2$$

### Explanation:

$$\frac{k}{\sqrt{3} + \sqrt{2}}$$ = k$$\sqrt{3 - 2}$$
$$\frac{k}{\sqrt{3} + \sqrt{2}}$$ x $$\frac{\sqrt{3} - \sqrt{2}}{\sqrt{3} - \sqrt{2}}$$
= k$$\sqrt{3 - 2}$$
= k($$\sqrt{3} - \sqrt{2}$$)
= k$$\sqrt{3 - 2}$$
= k$$\sqrt{3}$$ - k$$\sqrt{2}$$
= k$$\sqrt{3 - 2}$$
k2 = $$\sqrt{2}$$
k = $$\frac{2}{\sqrt{2}}$$
= $$\sqrt{2}$$

## Dicussion (1)

• $$\frac{k}{\sqrt{3} + \sqrt{2}}$$ = k$$\sqrt{3 - 2}$$
$$\frac{k}{\sqrt{3} + \sqrt{2}}$$ x $$\frac{\sqrt{3} - \sqrt{2}}{\sqrt{3} - \sqrt{2}}$$
= k$$\sqrt{3 - 2}$$
= k($$\sqrt{3} - \sqrt{2}$$)
= k$$\sqrt{3 - 2}$$
= k$$\sqrt{3}$$ - k$$\sqrt{2}$$
= k$$\sqrt{3 - 2}$$
k2 = $$\sqrt{2}$$
k = $$\frac{2}{\sqrt{2}}$$
= $$\sqrt{2}$$